Implementasi Strategi Advertising pada Platform Digital untuk Membangun Engagement di PT. Kreasi Kualitas Utama - Eczatio Rizkyanto Syardi Putra; Sahri Aflah Ramadiansyah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
This study discusses the implementation of advertising strategies on digital platforms to increase engagement at PT. Kreasi Kualitas Utama. The purpose of this research is to understand how the company applies digital advertising strategies to attract audience attention, enhance interaction, and build long-term relationships with consumers. This study uses a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation of the company’s digital marketing activities. The results show that PT. Kreasi Kualitas Utama utilizes various digital platforms such as Instagram, Facebook, and TikTok by implementing visual marketing, storytelling, and influencer collaboration to strengthen brand image and improve user engagement. In addition, consistency in content presentation and the use of interactive features play an important role in maintaining audience involvement. In conclusion, the implementation of well-planned digital advertising strategies oriented toward audience needs has proven effective in increasing engagement and expanding the company’s brand reach.